1976
DOI: 10.1093/oxfordjournals.aje.a112344
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Streptococcal Infections in a Defined Population of Children: Serotypes Associated With Skin and Respiratory Infections1

Abstract: Serial observations including cultures of the upper respiratory tract and of infected skin lesions and streptococcal antibody determinations were made over a two-year period in a semi-closed population of children between 10 months and 15 years of age. There was a high prevalence of group A streptococci in nose and throat cultures and of skin lesions containing these organisms. Almost 90% of the study population developed streptococcal impetigo during the study period. A slightly higher proportion of males tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…In agreement with previous studies, we found that the emm type distribution differed significantly between the different patient categories, which demonstrates a potential association between emm types and the kinds of infections (2,5,23). However, it should be recognized that although the differences may be explained by relative oversampling of some regions for invasive isolates or noninvasive isolates relative to the other, it seems unlikely that it could be the only explanation.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies, we found that the emm type distribution differed significantly between the different patient categories, which demonstrates a potential association between emm types and the kinds of infections (2,5,23). However, it should be recognized that although the differences may be explained by relative oversampling of some regions for invasive isolates or noninvasive isolates relative to the other, it seems unlikely that it could be the only explanation.…”
Section: Discussionsupporting
confidence: 92%
“…Decades of epidemiological findings support the existence of GAS strains that have strong preferences for either the throat or skin, as well as other strains whose tissue site preference is less clear cut (Anthony et al, 1976 ;Bisno & Stevens, 2000 ;Maxted, 1980 ;Wannamaker, 1970). Thus, there should exist tissuespecific genotypes among GAS strains.…”
Section: Abbreviationsmentioning
confidence: 99%
“…21 While it has been suggested that turnovers in military populations simply represent the effect of training class turnover events, 20 the data suggest otherwise. The sites studied here experience constant training class turnover, with approximately 10% of the recruit population being replaced weekly, yet specific emm types often dominate specific sites for periods of several months.…”
Section: Molecular Epidemiology Of Gas Among Military Recruitsmentioning
confidence: 99%
“…Dynamic epidemiology, characterized by rapid turnover between dominant strains, is the recognized pattern for GAS. 20,21 However, the scale on which these turnovers occur has not been well studied. Complete turnover between single dominant strains was seen in a small, somewhat isolated population of children, 21 while less succinct dynamic events were also seen in military recruits.…”
Section: Molecular Epidemiology Of Gas Among Military Recruitsmentioning
confidence: 99%
See 1 more Smart Citation